Nanoparticle tracking analysis - Peneder, H.; Punz, E.; Joubert, I.A.; Geppert, M.; Himly, M. (Open Schools Journal for Open Science, 2020)
Due to their extremely small size, nanoparticles cannot be analyses by conventional approaches such as light microscopy. To visualise particles in the nanoscale range, a combination of an ultra-microscope and a laser illumination unit has to be applied. This combinatory technique is called Nanoparticle Tracking Anlysis (NTA) and can be used of thr nalysis of particles in a size range of approximately 10 nm up to 1 μm in liquid suspension.